The Implementation of Vocabulary Learning Strategies In Students Vocabulary Size - Meliyana Junaid; Ummi Khaerati Syam; Uyunnasirah Hambali (English Language Teaching Methodology, 2023)
Using vocabulary size as a teaching strategy to help students improve their vocabulary is the primary goal of this study (in term noun and verb). At SMPN 1 Bide Satap, this study was carried out. In the following academic year, which will be 2021. Twenty-five second graders participated in this study. Purposive sampling was used to choose the sample. Class VIII has 25 pupils. There were a total of 25 students in the study. This study used a pre-experimental design with a single group pre-test and post-test. It was decided that Class VIII would be the experimental class for vocabulary size teaching. A vocabulary exam was utilized to get the data. The nouns t-test value is 4.869 and the verb t-test value is 4.47 with a frequency of db = 25-1 = 24 at a 50 percent significance level obtained t-table = 2,640, according to inferential statistical analysis using the t-test method. The null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted, if the t test is greater than the t table. In other words, the final post-test data reveals a significant improvement. We conclude that students who utilize vocabulary learning methodologies are able to increase their vocabulary size significantly